Family Perspectives on the Hospice Experience in Adult Family Homes - Washington, Karla T. (2011)
Growing numbers of terminally ill older adults receive hospice services in adult family homes (AFHs); however, little is known about the provision and receipt of end-of-life care in such environments. This paper reports findings from a qualitative exploration of family members’ perspectives of the hospice experience in AFHs. Analysis of data obtained during interviews of fifteen residents’ family members exposed significant challenges associated with transition to an AFH, highlighted the importance of AFH and hospice staff in family members’ assessment of overall quality of care, and emphasized the critical nature of communication in AFH settings.